Molecular analysis of the amphioxus frontal eye unravels the evolutionary origin of the retina and pigment cells of the vertebrate eye - Vopalensky, Pavel; Arendt, Detlev (Proceedings of the National Academy of Sciences of the United States of America, 2012)
The origin of vertebrate eyes is still enigmatic. The “frontal eye” of amphioxus, our most primitive chordate relative, has long been recognized as a candidate precursor to the vertebrate eyes. However, the amphioxus frontal eye is composed of simple ciliated cells, unlike vertebrate rods and cones, which display more elaborate, surface-extended cilia. So far, the only evidence that the frontal eye indeed might be sensitive to light has been the presence of a ciliated putative sensory cell in the close vicinity of dark pigment cells. We set out to characterize the cell types of the amphioxus frontal eye molecularly, to test their possible relatedness to the cell types of vertebrate eyes. We show that the cells of the frontal eye specifically coexpress a combination of transcription factors and opsins typical of the vertebrate eye photoreceptors and an inhibitory Gi-type alpha subunit of the G protein, indicating an off-responding phototransductory cascade. Furthermore, the pigmented cells match the retinal pigmented epithelium in melanin content and regulatory signature. Finally, we reveal axonal projections of the frontal eye that resemble the basic photosensory-motor circuit of the vertebrate forebrain. These results support homology of the amphioxus frontal eye and the vertebrate eyes and yield insights into their evolutionary origin.